A comparative study on the investment preferences of retail investors towards risky vs. non risky investment options - Manjunath, Mrs Vatsala; Bankar, Dr Bipin (The journal of contemporary issues in business and government, 2021)
Increasing presence of retail investors, in the Indian financial markets, calls for extensive study on their investment habits and behavior. The current study tries to understand the impact of the demographic characteristics of the individual investor on risk appetite, investment habits and selection of mutual funds as an investment choice. The study also investigates the impact of the demographic characteristics on choice of risky investment options Vs. Non risky options and all the investment options together. Statistical tests used have been used to conclude that the demographic variables age and income have an influence on the investment choice of mutual funds. Based on the results of tests conducted on the data collected it was found that income levels of a respondent have an influence on the selection of the risky investment choices. It has been found that the previous literature has mainly focused on the relation between the demographics and selection of mutual funds alone or only single class of financial instruments. The current paper has categorized the investment into risky and non-risky, to study the association of the categories with the demographics of the sample. However the test was conducted with a sample size of 100. The sample selection method used in the study was convenience sampling. Similar studies can be conducted with a larger sample size. Stratified sample or cluster sampling method or stratified sampling method could be used to have a better representation of the population. It would be interesting to study how the data would behave on a larger scale. Further studies in the same line are very important on many fronts .Considering the importance of the retail investor in a developing economy like India; the current study would help us to understand the retail investor better. A better understanding of the behavior of the end user, will help the finance professionals to design more custom made financial products in the coming future.